På ville veger? Levende utstillinger av samer i Europa og Amerika - Baglo, Cathrine (Universitetet i Tromsø, 2011)
During the nineteenth century new practices for the representation of otherness were established. A significant manifestation was the living exhibitions of Sami and other native peoples at “urban stages” in Europe and America. These exhibitions have usually been perceived as the western world’s staging of primitivity and race within hegemonic discourses based on exploitation and repression. In particular the exhibitions in zoological gardens have been considered instrumental in this respect. Although this dominant interpretation has provided important insight into how stereotypical features of cultural difference was normalized and naturalized, it has also seriously obscured the exhibitions own historicity and, in particular, the agency of the exhibited people themselves. In my dissertation I challenge this a priori victimizing approach to the living exhibitions. Through a detailed study of the Sámi participants and their exhibitors a far more nuanced picture of motivations, experiences and power relations emerges, also providing a richer account of the exhibitions’ own ethnography. I løpet av 1800- tallet vokste det fram en ny utstillingspraksis i den vestlige verden. Representanter for fremmede folkeslag, og det man etter hvert skulle begynne å tenke på som ”primitive” mennesker, ble brakt til Europa og Amerika hvor de opptrådte med sitt hverdagsliv for de besøkende. Også samer ble involvert i denne utstillingspraksisen. I løpet av årene 1822-1934(1950) deltok flere hundre. Disse utstillingene har ofte blitt sett på som et utelukkende negativt fenomen. Man har ofte antatt at deltakerne ble ensidig utnyttet, at de ikke visste hva de hadde begitt seg ut på, og at de gjennom utstillingene kun bidro til å skape eller opprettholde stereotypier om seg selv og egen kultur. I denne avhandlinga utfordrer jeg denne oppfatninga gjennom en detaljert kartlegging av de samiske deltakerne og deres utstillere, slik at et langt mer nyansert bilde av motivasjoner, erfaringer og maktforhold framtrer.